Lithography exposure characteristics of poly(methyl methacrylate) (PMMA) for carbon, helium and hydrogen ions - Nitipon Puttaraksa (2018)
Poly(methyl methacrylate) is a common polymer used as a lithographic resist for all forms of particle (photon, ion and electron) beam writing. Faithful lithographic reproduction requires that the exposure dose, Θ, lies in the windowΘ0≤Θ<Θ×0, whereΘ0and Θ×0represent the clearing and cross-linking onset doses, respectively. In this work we have used the programmable proximity aperture ion beam lithography systems in Chiang Mai and Jyväskylä to determine the exposure characteristics in terms of fluence for 2 MeV protons, 3 MeV4He2+and 6 MeV12C3+ions, respectively. After exposure the samples were developed in 7:3 by volume propan-2-ol:de-ionised water mixture. At low fluences, where the fluence is below the clearing fluence, the exposed regions were characterised by rough regions, particularly for He with holes around the ion tracks. As the fluence (dose) increases so that the dose exceeds the clearing dose, the PMMA is uniformly removed with sharp vertical walls. When Θ exceeds the cross-linking onset fluence, the bottom of the exposed regions show undissolved PMMA. © 2011 Elsevier B.V. All rights reserved.